2020
DOI: 10.1098/rstb.2020.0081
|View full text |Cite
|
Sign up to set email alerts
|

Temporal dynamics of competitive fertilization in social groups of red junglefowl (Gallus gallus) shed new light on avian sperm competition

Abstract: Studies of birds have made a fundamental contribution to elucidating sperm competition processes, experimentally demonstrating the role of individual mechanisms in competitive fertilization. However, the relative importance of these mechanisms and the way in which they interact under natural conditions remain largely unexplored. Here, we conduct a detailed behavioural study of freely mating replicate groups of red junglefowl, Gallus gallus , to predict the probability that competing mal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 126 publications
(215 reference statements)
1
17
0
Order By: Relevance
“…However, when individuals in a wild population are able to mate multiple times over the entire reproductive season, the number of sperm competing in a female’s reproductive tract may become more important than the morphology, velocity, or quality of those sperm cells. Males that mate frequently with the same or multiple females may have a competitive advantage, supplying fresh sperm to the female and potentially displacing other sperm from storage [ 89 , 90 ]. Though we did not detect significant selection on sperm morphology or velocity in this study, it could be that our measurements of sperm velocity and morphology were not sensitive enough to detect a relationship with fitness.…”
Section: Discussionmentioning
confidence: 99%
“…However, when individuals in a wild population are able to mate multiple times over the entire reproductive season, the number of sperm competing in a female’s reproductive tract may become more important than the morphology, velocity, or quality of those sperm cells. Males that mate frequently with the same or multiple females may have a competitive advantage, supplying fresh sperm to the female and potentially displacing other sperm from storage [ 89 , 90 ]. Though we did not detect significant selection on sperm morphology or velocity in this study, it could be that our measurements of sperm velocity and morphology were not sensitive enough to detect a relationship with fitness.…”
Section: Discussionmentioning
confidence: 99%
“…Birds have been at the center of the study of sperm competition for more than three decades [ 26 , 27 , 28 , 29 , 30 ], likely due to long-standing knowledge of extra-pair mating (i.e., mating outside the social pair bond) and consequent extra-pair paternity (EPP) [ 31 ]. Studies of domestic populations have provided key insights into the mechanisms of avian sperm competition [ 32 , 33 , 34 , 35 ], as well as the adaptive value of sperm traits.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, artificial insemination studies have shown that sperm motile performance influences male paternity success in mallards ( Anas platyrhynchos ) [ 41 ], while both sperm number and mobility shape fertilization success in red junglefowl ( Gallus gallus ) [ 42 ]. More recently, a study of red junglefowl held in freely mating groups showed that the male remating rate, mating order and timing of mating (i.e., last male advantage), and male age, as well as female resistance, shape a male’s probability of fertilization success, but that the importance and impact of these factors vary over time [ 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…The effects were found to be time-dependent as they became stronger over the course of experimental trials, indicating cumulative effects of different behavioural mechanisms. These data shed new light on the fine-scale dynamics of sperm competition in birds [60].…”
Section: Rapid Growthmentioning
confidence: 78%
“…Molecular paternity testing coupled with the accumulated knowledge and conceptual foundations of postmating sexual selection fuelled a rapid increase in research on this taxon, spurred on by Birkhead and Møller's volume Sperm competition in birds [32] published in 1992. In their contribution to this issue, Carleial et al [60] provide new data on sperm competition dynamics in red jungle fowl, finding that in free-ranging populations repeated mating and mating last with a given female are the principal factors determining a male's competitive fertilization success, while increased age, female resistance to copulation and her degree of polyandry all decrease a male's success in gaining fertilizations. The effects were found to be time-dependent as they became stronger over the course of experimental trials, indicating cumulative effects of different behavioural mechanisms.…”
Section: Rapid Growthmentioning
confidence: 99%